Encyclopedia of communication theory - Littlejohn, Stephen W.; Foss, Karen A. (Gale virtual reference library, 2009)
Provides students and researchers with a comprehensive overview of contemporary communication theory. Entries address topics related not only to paradigms, traditions, and schools, but also metatheory, methodology, inquiry, and applications and contexts.